COLOR WILL SHOW THE SAFETY AND RISK OF INVESTMENT: रंग बताएंगे निवेष की सुरक्षा और जोखिम - Mehta, Jyoti (International Journal of Research -GRANTHAALAYAH, 2014)
Rango is important in human life since ancient times, but with the advent of digital technology, the entire world of colors has become multi-faceted. Now the use and importance of colors are increasing in many areas of life, which give different types of signs. Now the importance of colors in the financial market is also increasing, especially when investing in mutual fund schemes, the colors shown for those schemes will guide the investors, indicating the risk of that scheme. Currently, the number of investors investing in mutual fund schemes is almost exclusively preferred by investors investing small sums of money, whereas mutual funds invest the money deposited from their investors in the shares and securities market. Where the risk associated with the market is involved. However, in comparison to investing directly in a stock, the risk in investing through mutual funds is somewhat less. प्राचीन काल से मानव जीवन में रंगो का महत्व है, लेकिन डिजिटल टेक्नोलाॅजी के आगमन के साथ रंगो की पुरी दुनिया ही बहुआयामी हो गई है। अब जिंदगी के अनेक क्षेत्रो में रंगो का उपयोग और महत्व बडता जा रहा है, जो विभिन्न प्रकार के संकेत देते है। अब फाइनेंषियल मार्केट में भी रंगो का महत्व बढने लगा है, विषेषकर म्यूचुअल फंड की योजनाओं में निवेष करते समय उन स्कीमो के लिये दर्षाए गए रंग उस स्कीम की जाखिम का संकेत देते हुए निवेषको का मार्गदर्षन करेंगे। वर्तमान में म्यूचुअल फंड की योजनाओं में निवेष करने वाले निवेषको की संख्या लगभग सुरक्षित रूप से छोटी रकम का निवेष करने वाले निवेषक म्यूचुअल फंड पसंद करते है, जबकी म्यूचुअल फंड अपने निवेषको से जमा की गई रकम का निवेष शेयरो तथा प्रतिभुति बाजार में करते है, जहाॅ बाजार से जुडा जाखिम शामिल रहता है। हालांकि कुल मिलाकर सीधे तौर पर किसी शेयर में निवेष करने के मुकाबले म्यूचुअल फंड के जरिए निवेष में इस प्रकार का जाखिम कुछ कम रहता है।